A case report of exogenous lipoid pneumonia associated with avocado/soybean unsaponifiables - Jacques BOUTROS; Marine MUZZONE; Jonathan BENZAQUEN; Michael LEVRAUT; Charles-Hugo MARQUETTE; Fanny ROCHER; Yann DIASCORN; Bernard PADOVANI; Véronique HOFMAN; Sylvie LEROY (BMC Pulmonary Medicine, 2019)
Abstract Background Exogenous lipoid pneumonia is a rare disease resulting from intra-alveolar accumulation of lipids of mineral, vegetal, or animal origin, that induce a foreign body type of inflammatory reaction in the lungs. Gastroesophageal reflux disease and other esophageal abnormalities have often been associated with this disease. Case presentation We herein report the case of an 83-year-old patient in whom a follow-up chest computed tomography scan, for a lingular consolidation, showed multifocal ground glass and consolidative opacities with areas of low attenuation, suggestive of exogenous lipid pneumonia. The patient had been on piascledine capsules (avocado/soybean unsaponifiables) for 20 years and had a hiatal hernia with documented gastroesophageal reflux disease. After thorough history taking, no other predisposing factors were found. The diagnosis was confirmed using oil red staining of bronchoalveolar lavage showing lipid-laden macrophages and extracellular lipid droplets. Conclusions To our knowledge, this is the first case of ELP secondary to avocado/soybean unsaponifiables in the literature.